Semi-insubordinate at-constructions in Norwegian: formal, semantic and functional properties - Beijering, Karin (Norsk Lingvistisk Tidsskrift, 2017)
This paper reports on a corpus investigation of one type of semi-insubordination in Norwegian, viz. semi-insubordinate at-clauses. That is, constructions that consist of a subordinate at-clause which is preceded by just one element. The study offers an overview of possible initial constituents in this construction on the basis of spoken and written corpus data. The data show that there are basically two types of initial elements in semi-insubordinate at-constructions: evaluative and discursive ones. The former include 'minimal matrices' conveying the speaker's attitudinal assessment of the at-clause. The latter comprises rhetoric elements denoting the speaker's reasoning towards the at-clause in relation to prior discourse. Semi-insubordinate at-clauses are problematic for traditional syntactic analyses as these constructions extend beyond the sentence level. Syntactically they are independent clauses, but pragmatically they are heavily dependent on prior context. It will therefore be argued that semi-insubordinate at-clauses are best accounted for as a discourse level phenomenon.